Researching writing across the lifespan: The value of literacy studies for highlighting social and contextual aspects of change. Issue Volume 10:(2018)Special Issue (17th January 2019) - Tusting, Karin; Barton, David; McCulloch, Sharon; Papen, Uta; Potts, Diane
Abstract : This paper highlights the importance, when researching writing across the lifespan, of addressing a range of aspects of social context which change over time, particularly focusing on tools, values, relationships and identities. It illustrates this argument by drawing on a range of empirical studies exploring different aspects of writing in university settings, working with adults at a range of levels from Masters through doctoral study to academics' working lives, and reflects on the implications of this research for lifespan writing studies more generally. The projects drawn on include a study of multimodal feedback on postgraduate student writing and students' responses to this; a detailed study of academics' writing practices in the context of structural changes in Higher Education; and an interview study with PhD students participating in writing retreats, reflecting on their writing experiences. Drawing on findings from this work, we argue that shifts in material, social and institutional dimensions of context have a significant impact on what individuals write and on the writing practices that they develop. We particularly highlight the role of changing tools for writing and values around writing, and the importance of transformations in identity and relationships. We argue that the tradition of literacy studies research, drawn on by all the projects described in this paper, provides the theoretical and methodological resources to approach such aspects of academic writing development across the lifespan, by adopting a holistic perspective on writing which locates writing as situated practice and thereby provides insight into these social and contextual influences.